2019
DOI: 10.1002/eap.1903
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐energetic modeling of medium‐sized cetaceans shows high sensitivity to disturbance in seasons of low resource supply

Abstract: Understanding the full scope of human impact on wildlife populations requires a framework to assess the population‐level repercussions of nonlethal disturbance. The Population Consequences of Disturbance (PCoD) framework provides such an approach, by linking the effects of disturbance on the behavior and physiology of individuals to their population‐level consequences. Bio‐energetic models have been used as implementations of PCoD, as these integrate the behavioral and physiological state of an individual with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(111 citation statements)
references
References 51 publications
2
109
0
Order By: Relevance
“…This conclusion is supported by analyses of the potential effects of body condition on vital rates using bioenergetics models. For example, Hin et al (2019) used a dynamic energy budget (DEB) model of the North Atlantic long-finned pilot whale to investigate the potential effects of disturbance on lifetime reproductive success. They found that disturbance could lead to a large reduction in the proportion of calves that survived to weaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is supported by analyses of the potential effects of body condition on vital rates using bioenergetics models. For example, Hin et al (2019) used a dynamic energy budget (DEB) model of the North Atlantic long-finned pilot whale to investigate the potential effects of disturbance on lifetime reproductive success. They found that disturbance could lead to a large reduction in the proportion of calves that survived to weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Body condition also varies markedly seasonally and during different life history stages. For example, the DEB model developed by Hin et al (2019) indicates that body condition (as estimated by the proportion of body mass available as an energy reserve) of undisturbed lactating pilot whales and their calves may fall to potentially lifethreatening levels during the first year of lactation. It is therefore important, whenever possible, to identify the life history stage of each individual when estimating its body condition.…”
Section: Understanding Natural Variationmentioning
confidence: 99%
“…Figure 3 shows the pooled distribution of the experts' predictions of the maximum number of days of disturbance that can be tolerated before it has any effect on calf survival for harbor seals, harbor porpoise, and bottlenose dolphins. If data on this tolerance is lacking it may be possible to obtain suitable values using expert elicitation or bio-energetic modeling (e.g., Hin, Harwood, & de Roos, 2019;McHuron, Costa, Schwarz, & Mangel, 2016). Clearly, this threshold will not be appropriate for all taxa: species with low body weights and high basic metabolic rates (such as rodents and songbirds) may only be able to tolerate short periods of disturbance, whereas large poikilotherms may be able tolerate much longer periods.…”
Section: Identifying a "Set Threshold" For Questionmentioning
confidence: 99%
“…Clearly, this threshold will not be appropriate for all taxa: species with low body weights and high basic metabolic rates (such as rodents and songbirds) may only be able to tolerate short periods of disturbance, whereas large poikilotherms may be able tolerate much longer periods. If data on this tolerance is lacking it may be possible to obtain suitable values using expert elicitation or bio-energetic modeling (e.g., Hin, Harwood, & de Roos, 2019;McHuron, Costa, Schwarz, & Mangel, 2016).…”
Section: Decision Framework Questionsmentioning
confidence: 99%
See 1 more Smart Citation